Going Further in Combating Transnational Bribery: Voluntary Disclosure and Federal Transparency in America's Foreign Corrupt Practices Laws - Joseph, Daniel Andrew (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The purpose of this research is to analyze the role of incentives and mitigation strategies related to voluntary reporting in enforcing anti-corruption laws, especially in the context of the Foreign Corrupt Practices Act (FCPA) in the United States. This study shows that voluntary disclosures made by companies in anti-corruption law enforcement, based on an in-depth literature review, play an important role in facilitating effective collaboration between business and government entities. This study shows that voluntary disclosures made by companies in anti-corruption law enforcement, based on an in-depth literature review, play an important role in facilitating effective collaboration between business and government entities. A company's decision to voluntarily report Foreign Corrupt Practices Act (FCPA) violations is a complex strategic move influenced by legal incentives, cost-benefit calculations, reputational risks, and financial impacts. Further research is needed regarding longitudinal studies to examine the long-term impact of voluntary reporting on corporate reputation and financial performance. This research underscores the importance of this study and its relevance in a global context that increasingly demands corporate transparency and accountability.